Factor associated with tobacco use among the adult population in Sarawak, Malaysia: a cross sectional study - Mizanur, Rahman; Mohd Taha, Arif; Mohd Fadzillah, Razak; Raili, Suhaili; Tambi, Zainab; Akoi, Cliffton; Peak, Debura; Hasienti, Hussein (Epidemiology Biostatistics and Public Health, 2015)
Introduction: Consumption of tobacco in any form is one of the leading causes of preventable mortality. The World Health Organization recommends that it should be monitored regularly. This study was designed to estimate the prevalence of tobacco use among the rural adult population in Sarawak and factors associated with it.